The art of Jane Orleman: childhood trauma and the discourse of sexual violence - Kwon, Hyunji (Journal of Gender Studies, 2023)
Jane Orleman (American, born 1942) is an artist and a survivor of child sexual abuse. Through paintings she created during therapy, Orleman rejects the gendered and patriarchal binaries between therapeutic art and professional art, which pit the private, feminine, and intuitive against the public, masculine, and intellectual. By analysing selected artworks from Orleman that embody her child self, young woman self, and alternative self, I propose that Orleman reflects on and challenges the pathology of sexual trauma along with the discourse of sexual violence as a political statement. Therefore, I argue that her art deserves to be part of a larger, counternarrative, anti-rape and anti-incest cycle in contemporary American art.
Keywords: Sexual violence; art; survivor; therapy; trauma

Unsettling homocolonial frames of remembrance: Two-Spirit and Indigiqueer interventions at the museum - Failler, Angela (Memory Studies, 2023)
This article considers a Two-Spirit and Indigiqueer protest at the Canadian Museum for Human Rights as a flashpoint that exposes problems with how memory-making institutions are incorporating lesbian, gay, bisexual, trans and queer issues into their programming and/or collections. The protest brings into relief the museum’s investment in a homocolonial framing of remembrance for the way in which the telling of lesbian, gay, bisexual, trans and queer ‘progress’ is entangled with a settler colonial political economy wherein the tokenistic inclusion of some queers into the sexual citizenry happens alongside the dispossession, devaluing and criminalizing of others. I then undertake some preliminary ‘curatorial dreaming’ upon two other interventions–commentaries uploaded to a digital story bank by a Two-Spirit and an Indigenous queer museumgoer, and the short film Woman Dress by Plains Cree artist TJ Cuthand. Along with the protest, the commentaries and the film unsettle homocolonial frames of remembrance and provide critical openings towards decolonial queer memory work at the museum.
Keywords: Bibliographie; Nettoyer

Against Sexual Violence in the Museum: Art, Curating, and Activism - Perry, Lara; Krasny, Elke (Journal of Cultural Analysis and Social Change, 2022)
Depictions of sexual violence are frequently found in the collections and displays of art museums, and material that represents and affirms violence against women often is displayed unchallenged. This article poses questions about how the presence of this material has been addressed in the relations between feminist activism against sexual violence, art made by artists responding to and participating in feminist activism, and the curatorial activities that have arisen to address the challenges that these activities present to art museums. The chapter investigates the 2021 exhibition Titian: Women, Myth and Power at the Isabella Stewart Gardner Museum and its handling of themes of rape in the central exhibit, Titian’s Rape of Europa; the history of themes of rape in feminist art since the 1970s and in exhibitions of this art that have taken place in museums in the last two decades; and curatorial engagements with sexual violence and rape in recent art exhibitions in the US and in the UK. The article argues that new strategies for the presentation and interpretation of artworks dealing with sexual violence are needed for museums to redress the patriarchal and colonial presence of sexual violence in their collection.
Keywords: Art Curating; Fine Arts; Museum; Museum Violence; Myriam; Rape; Sexual Violence; Visual activism

What else can a crush become: working with arts-methods to address sexual harassment in pre-teen romantic relationship cultures - Huuki, Tuija; Kyrölä, Kata; Pihkala, Suvi (Gender and Education, 2022)
Keywords: Myriam

Re-Cognizing Harassment with the Arts - Babulski, Timothy (Phenomenology & Practice, 2022)
Absent mechanisms of restorative justice, victims of sexual harassment, particularly those within the LGBT+ community that are already frequent targets of relational aggression, are unlikely to either report or reckon with the consequences of inappropriate workplace behaviors and discrimination. Written from the perspective of a masculinized bisexual whose encounter with a pervasive culture of sexual harassment and psychological abuse provoked suicidal ideation, this paper employs the artistic practices of illustration as a means of first re-cognizing and recognizing phenomena, a Ricœurean construct of narrative and a palimpsest of multivocal text and images to evoke the lived experience of harassment and an analytic layer to invoke the phenomenon. By drawing, writing, and thinking through the phenomenon, the marriage of artistic and phenomenological approaches allows both researcher and reader to confront the ‘painful truths’ that otherwise resist easy analysis.
Keywords: LGBTIQ; Myriam; Safe spaces; Teaching arts; Visual arts

“She’s just another pretty face:” sexual harassment of female photographers - Somerstein, Rachel (Feminist Media Studies, 2021)
This article examines sexual and gendered harassment among professional female editorial photographers, whose experiences have largely been under-researched. It draws on semi-structured interviews conducted between 2017–2019 with 17 female professional editorial photographers, aged 23–82, who work in a variety of beats. Sixteen of 17 interviewees encountered sexual harassment, with gendered harassment the most common. Harassers included professors, other photographers, colleagues, salespeople, subjects, and the general public, whom photographers encountered at school, work, while networking, and when using and buying gear. Largely, participants addressed the sexual and gendered harassment on an individual level, rather than reporting it to editors or other authorities. These findings add qualitative nuance to quantitative research that suggests physical risks and economic precarity may drive women from the profession.
Keywords: Bibliographie; Embodiment; Myriam; Nettoyer; Sexual harassment; female journalists; gender and work; photographers; photojournalism

#MeToo in Sweden: Museum Collections, Digital Archiving and Hashtag Visuality - Uimonen, Paula (Ethnos, 2020)
In October 2017, the Nordic Museum in Stockholm launched its #metoo collection. The aim was to capture the viral #MeToo campaign that in Sweden has been likened to a (feminist) revolution. Based on archival research, interviews and media analysis, this article explores public submissions to the #metoo collection and analyses the museum’s rationale for collecting what is considered to be difficult cultural heritage. Noting the absence of images in the collection, the article argues that the iconic hashtag #MeToo constitutes an alternative form of digital visuality, here termed hashtag visuality. Hashtag visuality, the article suggests, is an emerging form of visual representation that captures the multimodal logic of social media, blurring distinctions between texts and images. In Sweden, #MeToo hashtag visuality reveals the contradictory prevalence of structural sexism and sexual violence in a country with a national self-image of gender equality and a self-proclaimed feminist government, while affirming feminist agency.
Keywords: Digital cultural heritage; Myriam; feminist agency; online testimonies; sexual violence; viral campaign

Patriarchal pits: the gendered experiences of female concert photographers - Lough, Kyser (Journal of Gender Studies, 2020)
While the presence of women in photojournalism is increasing, the way they are treated by their male counterparts remains unbalanced. Drawing from feminist theory and embodiment, this study examines how the gendered experience plays out for women in a particular niche of photojournalism; concert photography. The restricted access of the music scene and the embodied nature of photojournalism combine to present unique barriers for women. In-depth interviews with male and female concert photographers show women still face a form of patriarchal oppression in the field. This is seen through gendered language, such as ‘one of the guys’ versus a ‘mom in the pit’, embodied actions such as direct sexual harassment or indirect benevolent sexism, and in how women are questioned when they identify themselves as a photographer.
Keywords: Bibliographie; Myriam; Nettoyer; Photojournalism; concert photography; embodiment; feminist theory

‘To draw light, you need shadow’: Using graphic art to counter gender based violence in Drawing the Line - Zare, Bonnie (South Asian Popular Culture, 2020)
Women in India cope with an ongoing sense of precarity owing to the frequency of street harassment and sexual violence; this impacts their freedom to travel and sense of autonomous agency. The December 2012 Nirbhaya case, the rape and fatal injury of a Delhi medical student, returned the subject of rape to public discourse leading to mass protests and, eventually, some stronger anti-rape laws; however, #metoo allegations surface weekly, and artists and activists are demanding that the trivialization of rape and verbal abuse stop and active steps be taken to dismantle the cultural scaffolding undergirding twomen's violation. In 2014 a collaboration by Zubaan Press (New Delhi) and the Goethe Institute (Germany) brought a group of Indian graphic artists together to create stories about women’s ground realities and the microaggressions they experience. The resulting publication, Drawing the Line: Indian Women Fight Back, contains fourteen vignettes which reveal the constraints women experience and also illuminate women’s capacity for resilience and boldness. This essay analyzes the forms of resistance imagined in these narratives, how particular stories illuminate slow violence, and what may be lost if we know little about the perpetrators who commit these acts against women.
Keywords: Essay; India; Indian women; Myriam; Sexual harassment; Gender; graphic novel; sexuality; violence

The Changing Roles of Female Visual Artists in Morocco - El Azhar, Samir (Journal of Global Initiatives: Policy, Pedagogy, Perspective, 2019)
Keywords: Myriam

When Artists Fall: Honoring and Admiring the Immoral - Archer, Alfred; Matheson, Benjamin (Journal of the American Philosophical Association, 2019)
Is it appropriate to honor artists who have created great works but who have also acted immorally? In this article, after arguing that honoring involves identifying a person as someone we ought to admire, we present three moral reasons against honoring immoral artists. First, we argue that honoring can serve to condone their behavior, through the mediums of emotional prioritization and exemplar identification. Second, we argue that honoring immoral artists can generate undue epistemic credibility for the artists, which can lead to an indirect form of testimonial injustice for the artists’ victims. Third, we argue, building on the first two reasons, that honoring immoral artists can also serve to silence their victims. We end by considering how we might respond to these reasons.
Keywords: Arts; Myriam; admiration; condonation; epistemic injustice; honor; silencing

Facing Sexual Harassment and Abuse in the Feminizing Museum - trivedi, nikhil; Wittman, Aletheia (Journal of Museum Education, 2018)
Despite the growing number of women in museums, the undervaluing of educational work traditionally associated with women, and labor largely done by women today, persists. This begs the question: in what other ways are women and femmes working in museums undermined despite their growing presence as workers and the emerging centrality of the educational role of museums? In society more broadly, we see how undervaluing women and their labor leads to a spectrum of treatment that can be considered violent. In this spectrum, we include pay and benefit disparities, disempowerment, and marginalization through sexist, homophobic, and transphobic comments and objectification, harassment, threats, verbal, physical, emotional, and financial abuse, and at the far end of the spectrum sexual assault and murder. In this article, we discuss data collected through a survey conducted about incidences of sexual abuse and harassment experienced by museum workers. We explore the results of the survey in relation to the gender-based division of labor and skills among the museum workforce. We look to the responses to this survey as a gauge of how much power women and gender non-conforming people have in their daily work lives in museums and propose actions that could increase empowerment and support.
Keywords: Bibliographie; Myriam; Nettoyer; Sexual violence; feminization; gender equity; labor; museum education; museum workers

Dick pics on blast: A woman’s resistance to online sexual harassment using humour, art and Instagram - Vitis, Laura; Gilmour, Fairleigh (Crime, Media, Culture, 2017)
This article brings to attention and explores women?s use of non-traditional forms of resistance to online sexual harassment. In this piece we use Anna Gensler?s Instagram art project Instagranniepants to examine how women are appropriating the language and practices of the cyber realm to expose online sexual harassment and to engender a creative resistance which is critical, comedic and entertaining. Drawing from interdisciplinary literature on witnessing, satire and shaming, we explore the techniques Gensler uses to not only document harassment but also resist, engage and punish those who seek to perpetrate it. This article problematises the stereotype of women as passive victims of online public spaces, and is critical of popular discourses that portray online spaces as exclusively risky and that position women as the natural victims of online violence. It concludes that a more nuanced account of women?s negotiation of online spaces is necessary, particularly as an overarching narrative of risk and victimisation undermines the liberatory potential of the online realm.
Keywords: Myriam; Résistance aux VACS

More Than Two-Spirit: Queer Indigenous Sovereignty and Survivance in Museums - Cooper, Caitlin Skye (Université de Washington, 2017)
Keywords: Bibliographie; Nettoyer

LGBTQ Welcoming Guidelines for Museums: developing a resource for the museum field - Leitch, Christopher; Youngs, Renae; Gavigan, Annette; Lesperance, Michael; Burns, William James; Cohen-Stratyner, Barbara; Hammond, Paul; Hansen, Jaden (Museums & Social Issues, 2016)
Beginning in 2014, the LGBTQ Alliance professional network of the American Alliance of Museums (AAM) met to develop and publish a broad set of LGBTQ Welcoming Guidelines for Museums. The authors sought to help museums be more inclusive of lesbian, gay, bisexual, transgender and queer staff and visitors. The Guidelines conform to the most recent established standards of professional practice in museums and touch on all areas of museum work; they may be viewed as part informational reference, part institutional self-assessment tool. The Guidelines were unveiled at the AAM’s 2016 annual meeting, and are now available at no charge online (http://www.aam-us.org/resources/professional-networks/lgbtq). The LGBTQ Alliance encourages readers to use and review the Guidelines and to make observations, critiques and corrections directly to the current chair, Mike Lesperance (mike@thedesignminds.com).
Keywords: Bibliographie; Coffre à outils; Lesbian; Nettoyer; bisexual; diversity; gay; inclusion; transgender

LGBT People and the UK Cultural Sector: The Response of Libraries, Museums, Archives and Heritage since 1950 - Vincent, John (Routledge, 2016)
This book examines the complex and conflicting relationships between LGBT people and our cultural and heritage organisations including libraries, museums and
Keywords: Bibliographie; Nettoyer

The art of Jane Orleman: childhood trauma and the discourse of sexual violence

The Changing Roles of Female Visual Artists in Morocco - Azhar, Samir El
Female artists are actively participating in the development and growth of visual arts in Morocco. This article seeks to highlight their important contribution in the Moroccan visual arts. It deals with the access of women to the field of visual art, delineates successive categories for understanding the types of work female artists have engaged in since the independence of the country in 1956, and the challenges that these artists have been facing. It focuses on the artistic experiences of specific artists, believed to be, representative of some historical era or artistic trend. Moreover, it tries to put these artists into a cultural and historical framework to contextualize their artistic production.